2013
DOI: 10.3109/13816810.2012.755553
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum ofRB1Mutations in Argentine Patients: 20-years Experience in the Molecular Diagnosis of Retinoblastoma

Abstract: This study enabled us to obtain information about molecular and genetic features of patients with retinoblastoma in Argentina and correlate them to their phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…Thus, a combinatorial approach of RNA-based techniques and massive parallel sequencing is recommended for cases where no RB1 alteration can be identified. Nevertheless, our mutation detection rate of 92.5% for unilateral tumors and 100% for bilateral tumors, are comparable to other studies that have employed direct sequencing and MLPA as a combinatorial approach towards determining the RB1 mutational status with detection figures ranging between 92–100% for Bilateral and 10–61% in unilateral cases [45,50,55,70,71]. The high detection rates of RB1 gene mutations reported in our study shows that conventional techniques are still effective as clinical screening methods for most RB cases even in the era of next-generation sequencing due to the type of mutations that occur frequently in this disease.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, a combinatorial approach of RNA-based techniques and massive parallel sequencing is recommended for cases where no RB1 alteration can be identified. Nevertheless, our mutation detection rate of 92.5% for unilateral tumors and 100% for bilateral tumors, are comparable to other studies that have employed direct sequencing and MLPA as a combinatorial approach towards determining the RB1 mutational status with detection figures ranging between 92–100% for Bilateral and 10–61% in unilateral cases [45,50,55,70,71]. The high detection rates of RB1 gene mutations reported in our study shows that conventional techniques are still effective as clinical screening methods for most RB cases even in the era of next-generation sequencing due to the type of mutations that occur frequently in this disease.…”
Section: Discussionsupporting
confidence: 87%
“…The genetic study has high impact on retinoblastoma patients as well as their families, as it allows genetic counseling and individualized treatment in addition to reducing the number of unnecessary examinations under anesthesia and diminishing costs. 8 Mutations with reading frame shift and nonsense mutations were more frequent in familial cases. [8][9][10][11][12] A study that followed 144 families during 20 years concluded that, in the majority of cases, the clinical presentation of retinoblastoma is related to the type of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxyribonucleic acid (DNA) was obtained from peripheral blood leukocytes using the cetyltrimethylammonium bromide (CTAB) method and from frozen tumors by treatment with proteinase K, phenol/chloroform purification and ethanol precipitation. Segregation analysis of five polymorphic loci within the RB1 gene included two restriction fragment length polymorphisms (RFLPs: BamHI and XbaI, introns 1 and 17), and three microsatellites (Rbi2, Rbi4 and Rb1.20 introns 2,4 and 20), it was performed as previously described [19].…”
Section: Dna Isolation and Genotyping Of Polymorphic Locimentioning
confidence: 99%
“…In a previous study we reported the results of our experience in retinoblastoma testing throughout 20 years, using a methodology that has evolved over the study period [19]. Here we present the results of RB1 mutations in retinoblastoma patients with different clinical presentations, some of them with a rare multicentric retinoblastoma or with a second nonocular malignancy, as well as the rare association of RB with Down syndrome.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation